Proactive Marketing Strategy: Exploring Marketing Strategies to Increase Occupancy through a Dynamic Sales Approach at Madani Hotel Medan - Siahaan, Maya; Brina, Melda (PT FORMOSA CENDEKIA GLOBAL, 2024)
Marketing strategy is an important aspect in the hotel sector to attract visitor interest. The research aims to investigate the marketing strategies implemented by the Management of Madani Hotel Medan to increase occupancy rates and income at the hotel. The focus of the research includes analyzing marketing strategies carried out by the marketing team, as well as identifying the strengths and weaknesses of Madani Hotel in attracting consumers, both those staying overnight and those using meeting room facilities. The research results show that the Madani Hotel marketing team implements various marketing programs, such as Sales Calls, determining hotel rates, preparing new price brochures, promotions through print media, organizing promotional packages, sales trip activities, radio talk shows, travel and company gatherings, shipping birthday cake and souvenirs, afternoon tea with friends, telemarketing to potential contacts, and participation in MATTA FAIR in Malaysia.